Facile residue analysis of recent and prehistoric cook stones using handheld Raman spectrometry. (9th October 2014) - Short, Laura; Thoms, Alston V.; Cao, Bin; Sinyukov, Alexander M.; Joshi, Amitabh; Scully, Rob; Sanders, Virgil; Voronine, Dmitri V.
<x xml:space="preserve">Abstract</x> We performed food residue analysis of fire‐cracked rock (FCR) from experimental and prehistoric earth ovens using a handheld Raman spectrometry. Progress in modern optical technology provides a facile means of rapid non‐destructive identification of residue artifacts from archaeological sites. For this study spectral signatures were obtained on sotol (Dasylirion spp.) experimentally baked in an earth oven as well as sotol residue on an experimentally used processing tool. Inulin was a major residue component. The portable handheld Raman spectrometer also detected traces of inulin on experimental boiling stones used to boil commercially obtained inulin. The Raman spectra of inulin and sotol may be useful as signatures of some wild plant residues in archaeology. Spectroscopic analysis of millennia‐old FCR from prehistoric archaeological sites in Fort Hood, TX revealed the presence of residues whose further identification requires improvement of current optical methods. Copyright © 2014 John Wiley & Sons, Ltd.